Flame Retardants, Hexabromocyclododecane (HCBD) and Tetrabromobisphenol A (TBBPA), Alter Secretion of Tumor Necrosis Factor Alpha (TNFα) from Human Immune Cells - Yasmin, Sharia (Arch Toxicol, 2018)
Hexabromocyclododecane (HBCD) and tetrabromobisphenol A (TBBPA) are flame retardants, used in a variety of applications, which contaminate the environment and are found in human blood. HBCD and TBBPA have been shown to alter the tumor killing function of natural killer (NK) lymphocytes and the secretion of the inflammatory cytokines interferon gamma (IFNγ) and interleukin 1 beta (IL-1β). The current study examined the effects of HBCD and TBBPA on secretion of the critical pro-inflammatory cytokine tumor necrosis factor alpha (TNFα) from human immune cells. Preparations of human immune cells that ranged in complexity were studied to determine if the effects of the compounds were consistent as the composition of the cell preparation became more heterogeneous. Cell preparations studied were: NK cells, monocyte-depleted (MD) peripheral blood mononuclear cells (PBMCs), and PBMCs. Exposure of NK cells to higher concentrations of HBCD (5 and 2.5 μM) caused decreased secretion of TNFα. However, when the cell preparation contained T lymphocytes (MD-PBMCs and PBMCs) these same concentrations of HBCD increased TNFα secretion as did nearly all other concentrations. This suggests that HBCD’s ability to increase TNFα secretion from immune cells was dependent on the presence of T lymphocytes. In contrast, exposures to TBBPA decreased the secretion of TNFα from all immune cell preparations regardless of the composition of the cell preparation. Further, HBCD-induced increases in TNFα secretion utilized the p38 MARK pathway. Thus, both HBCD and TBBPA may have the capacity to disrupt the inflammatory response with HBCD having the potential to cause chronic inflammation.